Salient features and outline of the joint Japanese guidelines for safe handling of cancer chemotherapy drugs - Kiyoko Kanda; Kazue Hirai; Keiko Iino; Hisanaga Nomura; Hisateru Yasui; Taro Kano; Chisato Ichikawa; Sumiko Hiura; Tomoko Morita; Ayako Mitsuma; Hiroko Komatsu (Elsevier, 2017)
The purpose of this paper is to introduce the outline and describe the salient features of the "Joint Guidelines for Safe Handling of Cancer Chemotherapy Drugs" (hereinafter, "Guideline"), which were published in July 2015. The purpose of this Guideline is to provide guidance to protect against occupational exposure to hazardous drugs (HDs) to all medical personnel involved in cancer chemotherapy, including physicians, pharmacists, and nurses and home health-care providers. The Guideline was developed according to the Medical Information Network Distribution Service guidance for developing clinical practice guidelines, with reference to five authoritative guidelines used worldwide. PubMed, Cumulative Index to Nursing and Allied Health Literature, Ichushi-Web, and Cochrane Central Register of Controlled Trials were used for a systematic search of the literature. Eight clinical questions (CQs) were eventually established, and the strength of recommendation for each CQ is presented based on 867 references. The salient features of the Guideline are that it was jointly developed by three societies (Japanese Society of Cancer Nursing, Japanese Society of Medical Oncology, and Japanese Society of Pharmaceutical Oncology), contains descriptions including the definition of HDs and the concept of hierarchy of controls, and addresses exposure control measures during handling of chemotherapy drugs. Our future task is to collect additional evidence for the recommended exposure control measures and to assess whether publication of the Guideline has led to adherence of measures to prevent occupational exposure.